Analisis Yuridis Permohonan Perwalian oleh Orang Tua dalam Pengurusan Izin Penjualan Tanah Harta Waris Anak di Bawah Umur: Studi Putusan Nomor 199/Pdt.P/2025/PN Blt - Alex Suhartanto; Weppy Susetiyo; M. Taufan Perdana Putra (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the juridical aspects of guardianship applications by parents to obtain permission to sell a minor’s inherited land and analyzes the judicial considerations in Decision Number 199/Pdt.P/2025/PN Blt. The research employs an empirical juridical method with a sociological legal approach. Primary data were collected through interviews and case documents at the Blitar District Court, while secondary data consist of statutes, doctrine, and related literature. Qualitative-descriptive analysis was applied to interpret the findings. The study reveals that the guardianship application process involves both administrative and judicial stages. Judges scrutinize material evidence and the probity of sale objectives, weighing important principles such as utility, legal certainty, fairness, and justice. Guardians are granted limited authority to sell a minor’s property only if it can be proven to be in the child's best interest and legal protections are assured. Recommendations include strengthening post-decision monitoring, enhancing legal outreach, improving procedural transparency, and ensuring comprehensive implementation.